PERANAN KEBIJAKAN PUBLIK TERHADAP PENGUATAN PENDIDIKAN KARAKTER SISWA - Florentinus Sudiran (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2018)
The aim of this research is to know the regulation of the Minister of Education and culture Number 23 , 2017 on the strengthen of the character of education by one day school in 5 days per week.The location of it is in Indonesia in September 2017 by using method of library one by taking the correlated news in the only resource namely Gatra magazines published n August 30,17 by reasoning is that the discription of it very interesting by the title THE WAYOUT TO STRENGTHEN THE CHARACTER and there are only some people have read this title .The results of it are (1).The one day school make polimic in the education society ,(2).The pro-ones said that the one dy school (a).It can give oPeraturan Pemerintahortunity to strengthen the students’s character ,(b). It can give one day to gether with their parents on Saturday , (c).The parents can catch-up the children at 5 o’clock PM from their offices and together home ,(3).The contra by giving any argument,(a).It makes the students tired and boring with ,(b).The program for 6 days school can cover the strengthenness of the students’ charchter,(c).Some schools have arranged the activity of deepening their religion in such that the program can go well.The suggestions are ,(1).The schools can choose the the best for them ,(2).This regulation may not become polemic because can make chaos,(3).The parents can be given the problem solving ,(4).The government has to make president’decision to prevent the chaos.(5).